2019
DOI: 10.1080/16000870.2019.1606666
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the uncertainty of areal precipitation using data assimilation

Abstract: We present a method to estimate spatially and temporally variable uncertainty of areal precipitation data. The aim of the method is to merge measurements from different sources, remote sensing and in situ, into a combined precipitation product and to provide an associated dynamic uncertainty estimate. This estimate should provide an accurate representation of uncertainty both in time and space, an adjustment to additional observations merged into the product through data assimilation, and flow dependency. Such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The climatic variables were positively correlated with the tea yield [6,[24][25][26]. Among the climate factors, temperature variability was determined as a stronger positive effect than precipitation in the predicted tea yield [43,51,54]. In our study, NDVI and mean temperature played a more important role than the other variables for estimating yield (Figure 8), which can be attributed to the different order as follows: mean temperature > NDVI > Tmin > precipitation > Tmax > solar radiation.…”
Section: Limitation and Future Perspectivesmentioning
confidence: 54%
See 1 more Smart Citation
“…The climatic variables were positively correlated with the tea yield [6,[24][25][26]. Among the climate factors, temperature variability was determined as a stronger positive effect than precipitation in the predicted tea yield [43,51,54]. In our study, NDVI and mean temperature played a more important role than the other variables for estimating yield (Figure 8), which can be attributed to the different order as follows: mean temperature > NDVI > Tmin > precipitation > Tmax > solar radiation.…”
Section: Limitation and Future Perspectivesmentioning
confidence: 54%
“…Van Leeuwen et al [52] confirmed that MODIS NDVI data were affected by atmospheric water vapor, even though this effect was minimal. In addition, the uncertainty, particularly in precipitation, and in general, meteorological have been addressed by Savino Curci et al [53] and C.Merker et al [54]. These uncertainties of data can develop in the near future when considering the error of various variable input in the prediction yield.…”
Section: Limitation and Future Perspectivesmentioning
confidence: 99%